Smart Weather Monitoring Station - Mohan M. Khambalkar; Anitta N. Bhatt; Ibrahim Koicha; Priya Tandel; Mohit Gidwani (International Journal of Satellite Remote Sensing, 2024)
Climate change and the environment have been in attention lately. Therefore, it is essential to track the real-time weather conditions of one location from a different one. The Internet of Things (IoT) plays a crucial role in measuring these parameters by utilizing sensor networks that cover the surrounding environment. The Internet of Things is the next miracle of the Internet that will change the lifestyle of the people. It extends connectivity far beyond just phones and computers to include virtually any device with a chip and a data interface. The Internet of Things (IoT) collects data from electronic sensors and is designed to transmit this data to the cloud for storage and analysis across various applications. This paper demonstrates real-time monitoring of temperature, humidity, and air quality using IoT on the Thing Speak cloud, incorporating temperature and pressure sensors integrated with the cloud platform. Accordingly, we have added alert system via which the alert can be received by the signed person and major accidents can be avoided. As well the live data can be viewed via a web application designed specifically which will help to know particular data of the given location at a particular time.
Keywords: Cloud platform; Embedded system; Internet of Things; NodeMCU; data analysis; thing speak platform; web application